2021
DOI: 10.3390/antiox10071055
|View full text |Cite
|
Sign up to set email alerts
|

Novel Extract from Beetle Ulomoides dermestoides: A Study of Composition and Antioxidant Activity

Abstract: A biologically active extract from the darkling beetle Ulomoides dermestoides was obtained using the electro-pulse plasma dynamic extraction method. The beetle water extract contained a complex of antioxidant substances such as antioxidant enzymes and nonprotein antioxidants, as well as a complex of heat shock antistress proteins. This determines the rather high antioxidant activity of the aqueous extract of the beetle, i.e., 1 mg of dry matter/mL of the extract has an equivalent antioxidant activity to 0.2 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…Insects are a natural source of substances with biological activity, including antibacterial, antiviral, and anti-inflammatory activities [7]. In traditional medicine, some species of edible insects are used to treat inflammatory diseases [8,9]. Stull et al found that eating a breakfast enriched with 25 g of cricket powder for 2 weeks reduced circulating levels of the pro-inflammatory cytokine TNF-α in the plasma of 20 healthy adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…Insects are a natural source of substances with biological activity, including antibacterial, antiviral, and anti-inflammatory activities [7]. In traditional medicine, some species of edible insects are used to treat inflammatory diseases [8,9]. Stull et al found that eating a breakfast enriched with 25 g of cricket powder for 2 weeks reduced circulating levels of the pro-inflammatory cytokine TNF-α in the plasma of 20 healthy adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained gel fragments were washed 2 times for 15 min with 100 μL of 50 mM ammonium bicarbonate solution, then dried with 100% acetonitrile (15 min), after which the solution was removed, and the samples were dried on a centrifugal vacuum evaporator (Concentrator Plus, Eppendorf). Proteins in each gel fragment were distained and digested by trypsin using the protocol described previously 65 , 66 .…”
Section: Methodsmentioning
confidence: 99%
“…An isolation intensity threshold of 50,000 counts was determined for precursor’s selection and up to top 20 precursors were chosen for fragmentation with high-energy collisional dissociation (HCD) at 29 NCE. Precursors with a charge state of 1+ and more than 5+ were rejected and all measured precursors were dynamically excluded from triggering of a subsequent MS/MS for 90 s 65 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations